Disseminated Tuberculosis in An Immunocompetent Patient Presenting with Ptosis and Diplopia: A Case Report - Zahra, Nadhifa Az; Pradnyandari, Anak Agung Sagung Putri; Kusmiati, Tutik; Widjaja, Stella Agatha (Jurnal Respirasi, 2025)
Introduction: Tuberculosis (TB) remains a global health burden to this day, with pulmonary TB (PTB) being one of its most common types. A lapse in the host immune response may lead to the dissemination of TB infection, causing extrapulmonary TB (EPTB) that is more difficult to manage, as it frequently shows atypical complaints. However, its manifestations among immunocompetent patients are rarely well-investigated. Case: A 28-year-old human immunodeficiency virus (HIV)-negative woman presented with a history of chronic progressive bilateral headache, followed by diplopia and ptosis of her left eyelid. She also had classical TB symptoms 3 months prior. She had a history of household tuberculous contact for years, but she was never tested for TB nor given an anti-TB treatment (ATT). Chest X-ray revealed cavities and pleural thickening in the apex of the left lung. Contrast-enhanced magnetic resonance imaging (MRI) of the brain showed multiple intracranial tuberculomas and meningeal enhancement in most brain areas. GeneXpert tests from both sputum and cerebrospinal fluid (CSF) suggested TB infections. She was later diagnosed with simultaneous tuberculous meningoencephalitis (TBME) and PTB. After a 17-day course of oral ATT, streptomycin injection, and intravenous corticosteroid, she was discharged with improved clinical conditions and scheduled for outpatient follow-up until she completed 12 months of ATT. Conclusion: In immunocompetent patients, disseminated TB is an uncommon occurrence and is frequently characterized by atypical symptoms. Findings from this case emphasize that comprehensive assessment and timely therapeutic intervention are critical for minimizing morbidity and mortality of TB infection.